2013
DOI: 10.1080/03632415.2013.836501
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Fishery‐Induced Collapse of Invasive Asian Carp in the Illinois River

Abstract: Prospectos de un colapso inducido por pesca en la carpa asiática del Río Illinois RESUMEN: . La carpa asiática amenaza con invadir el Lago Michigan a través del sistema de vías acuáticas del área de Chicago, lo cual podría acarrear serias consecuencias en las tramas tróficas de los grandes lagos. Además de los esfuerzos llevados a cabo para impedir el ingreso de estos peces al Lago Michigan mediante barreras eléctricas, el estado de Illinois ha iniciado un programa de pesca en el Río Illinois, cuya finalidad e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 33 publications
1
87
1
Order By: Relevance
“…If enhanced commercial harvest is restricted to the Illinois River, it appears likely that immigrants would replenish Silver Carp stocks in the Illinois River without additional efforts to limit fish movement such as installation of barriers at dams (Conover et al 2007) given the substantial contribution of recruits from the middle Mississippi River to all three reaches of the Illinois River. Our findings regarding recruitment sources of Bighead and Silver carps in the Illinois River will be important for refining recently developed simulation models for predicting population responses to harvest and development of spatially-explicit strategies to achieve fishery-induced collapse (Tsehaye et al 2013). We also anticipate that otolith microchemistry and stable isotope analyses may be applicable to other portions of the expanding, non-native ranges of Bighead and Silver carps to identify their principle recruitment sources and inform development of control strategies to limit their range expansion and impacts.…”
Section: Differences In Water Srmentioning
confidence: 99%
See 2 more Smart Citations
“…If enhanced commercial harvest is restricted to the Illinois River, it appears likely that immigrants would replenish Silver Carp stocks in the Illinois River without additional efforts to limit fish movement such as installation of barriers at dams (Conover et al 2007) given the substantial contribution of recruits from the middle Mississippi River to all three reaches of the Illinois River. Our findings regarding recruitment sources of Bighead and Silver carps in the Illinois River will be important for refining recently developed simulation models for predicting population responses to harvest and development of spatially-explicit strategies to achieve fishery-induced collapse (Tsehaye et al 2013). We also anticipate that otolith microchemistry and stable isotope analyses may be applicable to other portions of the expanding, non-native ranges of Bighead and Silver carps to identify their principle recruitment sources and inform development of control strategies to limit their range expansion and impacts.…”
Section: Differences In Water Srmentioning
confidence: 99%
“…Age-0 bigheaded carps have also been collected from connected floodplain lakes along the Illinois River (Pegg et al 2002;DeGrandchamp et al 2007); however, the relative importance of these floodplain lakes and low-velocity river channel margin habitats as nursery areas for Bighead and Silver carps is also unknown. A recently developed simulation model indicated that harvesting all sizes of Bighead and Silver carps is required to achieve fishery-induced collapse (Tsehaye et al 2013). Thus, improved understanding of natal environments and early life habitat use of Bighead and Silver carps is particularly important to determine the appropriate spatial scale for enhanced commercial harvest and other control measures and to direct such efforts to areas that contribute substantially to recruitment of these species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying feeding ecology of BC and SC is helpful to control fish yields depending on the trophic conditions of water bodies not only within China, but also worldwide where they play a major role in food security of rural people (Sugunan and Katiha 2004;Wijenayake et al 2005;Rahman et al 2012). Also, it is useful in places where these fish species should be managed in order to control either eutrophication levels of water bodies or protect indigenous species from invasion threats (Yang et al 2006;Ma et al 2010;Tsehaye et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This practice has been followed in eutrophication control work as well (Chen et al 2006;Ke et al 2008). However, due to their rapid growth rate, efficient feeding habits, ability of adaptation to new environments and competition with native filter-feeders, they also have been considered as invasive species in some parts of the world, and subject to management accordingly (Chen et al 2006;Tsehaye et al 2013).…”
Section: Introductionmentioning
confidence: 99%